AML-262 Pivekimab Sunirine (PVEK, IMGN632) triplet with azacitidine and venetoclax shows broad activity in adverse genetic subsets of relapsed/refractory acute myeloid leukemia and reduced infusion-related reactions - Daver, N; Montesinos, P; Aribi, A; Martinelli, G; Altman, JK; Wang, ES; Roboz, GJ; Burke, PW; Gaidano, G; Walter, RB; Thomas, X; Jeyakumar, D; et al. (Elsevier, 2022)
Context: Pivekimab sunirine (PVEK, IMGN632) is a first-in-class ADC comprising a CD123 high-affinity antibody, a cleavable linker, and an IGN (indolinobenzodiazepine pseudodimer) payload. PVEK with azacitidine (AZA) and venetoclax (VEN) is a novel triplet that has demonstrated anti-leukemia activity in relapsed/refractory AML patients.